How often do both core competencies of shared decision making occur in family medicine teaching clinics? - Diendéré, Gisèle (Can Fam Physician, 2019)
OBJECTIVE: To assess how often risk communication and values clarification occur in routine family medicine practice and to explore factors associated with their occurrence. DESIGN: Qualitative and quantitative cross-sectional study. SETTING: Five university-affiliated family medicine teaching clinics across Quebec. PARTICIPANTS: Seventy-one health professionals (55% physicians, 35% residents, 10% nurses or dietitians) and 238 patients (76% women; age range 16 to 82 years old). MAIN OUTCOME MEASURES: The presence or absence of risk communication and values clarification during visits in which decisions were made was determined. Factors associated with the primary outcome (both competencies together) were identified. The OPTION5 (observing patient involvement in decision making) instrument was used to validate the dichotomous outcome. RESULTS: The presence of risk communication and values clarification during visits was associated with OPTION5 scores (area under the curve of 0.80, 95% CI 0.75 to 0.86, P < .001). Both core competencies of shared decision making occurred in 150 of 238 (63%) visits (95% CI 54% to 70%). Such an occurrence was more likely when the visit included discussion about beginning something new, treatment options, or postponing a decision, as well as when health professionals preferred a collaborative decision-making style and when the visit included more decisions or was longer. Alone, risk communication occurred in 203 of 238 (85%) visits (95% CI 82% to 96%) and values clarification in 162 of 238 (68%) visits (95% CI 61% to 75%). CONCLUSION: Health professionals in family medicine are making an effort to engage patients in shared decision making in routine daily practice, especially when there is time to do so. The greatest potential for improvement might lie in values clarification; that is, discussing what matters to patients and families.